ALIRAN HERMENEUTIKA, PENERAPANNYA DALAM ULUMUL QUR’AN, DAN TIPOLOGI PENAFSIRAN KONTEMPORER - Hasbi Maulana (Dirasat: Journal Islamic Studies, 2025)
This study examines the dynamic relationship between hermeneutical schools of thought and the development of Ulumul Qur’an within the landscape of contemporary Qur’anic interpretation. Hermeneutics is approached as a framework that enables dialogue between the historical meaning of the text and the interpretive demands of the modern era. Concepts such as the horizon of understanding, the hermeneutical circle, the double movement, and the ma’na-cum-maghza are employed to reread classical Qur’anic sciences in a more contextual manner. The literature reveals that hermeneutics significantly enriches the understanding of asbab al-nuzul, nasikh-mansukh, and textual coherence by incorporating socio-historical considerations and interpretive dynamics. Contemporary trends in Qur’anic interpretation show three prominent orientations: conservative quasi-objectivism, subjectivism, and progressive quasi-objectivism, each offering distinct ways of relating divine revelation to current realities. The study affirms that hermeneutics can be adapted into an interpretive model that preserves the sacred authority of the Qur’an while enabling interpretations that are relevant, flexible, and responsive to modern challenges.